Literature Review: Impact of Brand Image, Product Quality and Pricing on Consumer Buying Decision - Mochammad Mukti Ali; Nurul Syafrina Hardan (Dinasti International Journal of Education Management And Social Science, 2025)
Abstract: This study delves into how brand image, product quality, and pricing interact to shape consumer choices, especially within healthcare. The central question explores their combined effect on behavior in a competitive setting. A mixed approach was used consumer surveys for quantitative data and interviews for qualitative insights, ensuring a comprehensive view. Results show brand image greatly boosts trust and loyalty; perceived quality and pricing also heavily sway decisions. It turns out, a robust brand image often justifies a higher price, showing healthcare consumers value reliability and credibility. These findings matter a lot. They underscore the importance of strong branding and quality in healthcare marketing. Healthcare providers and manufacturers, therefore, must strategically balance these elements to boost sales and keep customers happy. Further, the study indicates healthcare organizations should embrace an integrated marketing strategy aligning image, quality, and pricing to build confidence and enable informed consumer decisions. Ultimately, such insights can refine marketing approaches and policies in healthcare, boosting patient engagement and satisfaction, with considerable effects on healthcare delivery and product advancements.